circNR3C1 Suppresses Bladder Cancer Progression through Acting as an Endogenous Blocker of BRD4/C-myc Complex - Fei Xie; Xingyuan Xiao; Dan Tao; Chao Huang; Liang Wang; Feng Liu; Hui Zhang; Haitao Niu; Guosong Jiang (Elsevier, 2020)
Bromodomain-containing protein 4 (BRD4), the core component of transcriptional regulatory elements, plays a significant role in tumorigenesis and aggressiveness. However, the mechanisms regulating the functions of BRD4 in bladder cancer (BC) still remain elusive. Herein, we identify one exonic circular RNA (circRNA) generated from NR3C1 gene (circNR3C1) as a regulator of BRD4/C-myc complex. Our previous study indicated that BRD4 and C-myc promoter region form a complex, allowing C-myc to function as a transcription factor for BC progression. In the present study, mechanism studies reveal that circNR3C1 could interact with BRD4 protein, dissociating the formation of BRD4/C-myc complex. In vivo, ectopic expression of C-myc partly reverses the tumorigenesis of xenografts circNR3C1-induced in nude mice. Conclusively, these results demonstrate that circNR3C1 inhibits BC progression through acting as endogenous blocker of BRD4/C-myc complex.